Analysis of the energy efficiency promoted by the implementation of solar panels in hospitals in brazil and other countries - Oliveira, Joyce Éllen Santos de; Ramos, Heidy Rodriguez (National Journal of City Management, 2021)
The growing world’s population demands large electric energy production for the functioning and development of the modern society. With the increase of energy consumption and environmental changes caused by these processes, it is fundamental that public and private sectors search for alternative energy sources, which must be not only sustainable but also efficient for the development of their activities. In this context, renewable energy causes less impact to the environment, mitigating the emission of gases that contribute to the greenhouse effect. Among the main renewable energy sources, the photovoltaic solar energy stands out, with the advantage of being installed in small spaces and requiring minimum changes in such spaces. The photovoltaic solar system is one of the alternative energy options that have received considerable investments worldwide, because solar radiation is an abundant and inexhaustible energy source incident on the Earth’s surface. Large buildings, such as hospitals, despite being essential to well-being and health care, present a great polluting potential, in the sense that they may cause indirect hazards to the environment, due to the amount of energy that they need to perform a series of procedures. The present study aims to present the main projects of photovoltaic solar energy implementation that aimed at energy efficiency in hospitals. The study is based on bibliographic research and adopted a qualitative approach to assess study cases in Brazil and in some other countries. Among the main results, the projects implemented in hospitals in Europe, Africa and Brazil are highlighted, because of the attested efficiency reached after the implementation of photovoltaic solar panels, minimizing the amount of CO2 launched in the atmosphere and achieving energy and financial savings.